Coping with bereavement: The experience of a Filipino who lives life using a wheelchair. Issue 1 (2nd January 2021) - Yao, Daryl Patrick G.; Bontje, Peter; Inoue, Kaoru; Tanaka, Aoi; Lacsamana-Manalaysay, Jeana
ABSTRACT: Individuals with spinal cord injury are vulnerable to developing mental health issues, as their capability to participate in occupations for coping with life stressors, such as bereavement, is altered. However, the interplay of facilitators and constraints to participating in occupations is not well-known, especially in developing countries like the Philippines. The aim of this paper is to provide an understanding of how facilitators and constraints towards participation in occupation impact the mental health of an individual with spinal cord injury within the context of coping with bereavement. This study employed a single-case participatory action research method with narrative analysis. The result revealed how environmental inaccessibility and attitudes induced negative experiences of coping with bereavement, mitigable by supportive contexts. In conclusion, mental health and participating in occupations are hindered and supported by the contexts. Practitioners should diminish constraints and maximise facilitators to enhance participation in occupations and mental health.